Disasters risk and knowledge's management from a local perspective (2007)
It deals with the disasters risk's evaluation, from the Moa municipality local development's perpective, in Holguin, Cuba. The studies made are part of an investigation project carried out by specialists of the social area of the humanities school and the environmental mining energy's center. Some consultations and surveys to the community and the regional organism were done which contributed with significant results to the studies, base upon which measures were taken to contribute to the mining development of the Moa region. It is a model that can be applied in other regions of the country.